A Systematic Review of Genetic Influences on Coping. (January 2015) - Dunn, Sandra H.; Conley, Yvette P.
Coping refers to the way that an individual manages stress. Coping strategies vary; for example, problem-focused coping is directed at reducing or removing a stressor, while emotion-focused coping is directed more at managing reactions that accompany the stressor. How individuals cope with stress can impact their health, but the physiological effects of coping are not well understood. The field of genetics provides tools that could help illuminate the physiology of coping. This review of the literature was conducted to determine what is currently known about the phenotype of coping from a genetic perspective. PubMed, HubMed, PsychInfo, Medline, Scopus, and Google Scholar databases were used to conduct the search, and reference lists were reviewed to identify additional publications. Only studies that measured coping style or a coping domain specifically, were written in English language, and were human-subject focused were included in the review. We identified 19 studies that met these criteria, and 2 types of genetic studies emerged for the review: heritability ( n = 9) and candidate gene association ( n = 10) studies. Heritability estimates of .68–.76 support a nonadditive genetic component to coping. Replication of association was found for the serotonin transporter and adrenergic receptor beta 2 genes. In addition to finding evidence supporting a role for genetic variability with coping phenotype, it is worth noting that the review revealed a lack of consistency in instruments used to phenotype coping across studies.